The role of deep vadose zone water in tree transpiration during drought periods in karst settings – Insights from isotopic tracing and leaf water potential - Carrière, Simon Damien; Martin-StPaul, Nicolas K.; Cakpo, Coffi Belmys; Patris, Nicolas; Gillon, Marina; Chalikakis, Konstantinos; Doussan, Claude; Olioso, Albert; Babic, Milanka; Jouineau, Arnaud; Simioni, Guillaume; Davi, Hendrik (The Science of the total environment, 2020)
[Display omitted] •Mediterranean forest in karst environment exploits deep water in vadose zone.•Beech, Silver Fir, and Holm Oak exhibit different strategies in groundwater use.•Importance of including deep water resources in ecohydrological models Karst environments are unusual because their dry, stony and shallow soils seem to be unfavorable to vegetation, and yet they are often covered with forests. How can trees survive in these environments? Where do they find the water that allows them to survive? This study uses midday and predawn water potentials and xylem water isotopes of branches to assess tree water status and the origin of transpired water. Monitoring was conducted during the summers of 2014 and 2015 in two dissimilar plots of Mediterranean forest located in karst environments. The results show that the three monitored tree species (Abies alba Mill, Fagus sylvatica L, and Quercus ilex L.) use deep water resources present in the karst vadose zone (unsaturated zone) more intensively during drier years. Quercus ilex, a species well- adapted to water stress, which grows at the drier site, uses the deep water resource very early in the summer season. Conversely, the two other species exploit the deep water resource only during severe drought. These results open up new perspectives to a better understanding of ecohydrological equilibrium and to improved water balance modeling in karst forest settings.